Dietary fatty acid patterns and risk of metabolic syndrome: Tehran lipid and glucose study - Parvin Mirmiran; Zahra Gaeini; Zahra Feizy; Fereidoun Azizi (European Journal of Medical Research, 2023)
Abstract Background The association between individual dietary fatty acids (FAs) and risk of metabolic syndrome (MetS) has been investigated in previous studies. However, synergistic or additive effects of multiple FA have received less attention. Hence, we aimed to determine the major dietary FA patterns and evaluate the association between FA patterns and risk of MetS. Methods Dietary intakes of 1713 MetS-free adults who participated in the third phase of the Tehran Lipid and Glucose Study (TLGS) were assessed using a validated 168-items food frequency questionnaire. FA patterns were obtained by principal component analysis (PCA). Adjusted Hazard Ratios (HRs) and 95% confidence intervals (CIs) were calculated for the association of MetS incident with the extracted FA patterns. Results Four major FA patterns were identified through PCA of the 24 FAs consumed: “short- and medium-chain saturated fatty acid (SFA) pattern”, “long-chain FA pattern”, “omega-3 PUFA pattern”, and “long-chain SFA pattern”. There was no significant association between dietary FA patterns and risk of MetS incidence. Conclusions We found no significant association between FA patterns and risk of MetS. More prospective cohort studies and clinical trials are needed to clarify the issue.